Il munus sanctificandi alla prova del coronavirus Un “rinnovatoµ diritto canonico per una “nuovaµ realtà - Tarantino, Daniela (Salute umana e tradizioni religiose di fronte alle emergenze sanitarie, 2021)
The health emergency from Covid-19 has limited, especially during the lock down, the participation of the faithful in the liturgies and sacraments, stimulating the Catholic Church to work to find ways and times to respond to the emergency context, following the “signs of the timesµ and adapting the forms of development of the munera ecclesiae, first of all the munus sanctificandi, in order to pursue the salus animarum. In this context, the sacraments of the Eucharist and of Reconciliation are of central importance, since they place greater emphasis on the inseparable link between the formal and substantial aspects of law, particularly in a legal system such as the canonical one, that applies aequitas as a means for its own updating.